MANAJEMEN PENINGKATAN MUTU LULUSAN - Yean Chris Tien (UNIVERSITAS BENGKULU, 2015)
This study aimed to describe management of graduates’ quality improvement in State Elementary School 2 Selangit Musi Rawas. The method of the study is qualitative descriptive. The subjects of the study are the principal, vice principal and teachers. The results of the study are: (1) Planning going well. (2) Organizing clearly visible in the division of duties of teachers and school programs. (3) Implementation, including: infrastructure, facilities that support learning, programs, curriculum and lesson plans. (4) Monitoring and evaluation is done technically by the school superintendent, principals and community.Keyword: management, graduates, quality, improvement